Pagoh EduHub Aquatic Centre Water PH Monitoring Application - Nurhanan Syafiqah Suhaimi; Nur Elysha Atiqah Azhar; Nurul Azwany Abd Hussin; Kassim, Noordiana (Multidisciplinary Applied Research and Innovation, 2025)
Protecting water supplies becomes essential for our future as a species, not just our obligation. One location where hygienic issues are constantly present is the swimming pool. Swimming pools require a large amount of clean water for various water-related activities, but there is a challenge in maintaining hygiene. In this case, a pH scale is essential and this project aims to develop a basic monitoring application for the Pagoh Eduhub Aquatic Centre using Internet of Things (IoT) technology. The primary objective of the application is to track the pH level, which indicates the water quality and acidity, in the swimming pool. By offering real-time data on the pH of the water, the app seeks to facilitate the work of pool staff. It also helps staff maintain the water’s safety for public usage by keeping it between 7.0 and 7.6, to prevent hygiene and health issues for users. The research was done to identify the requirements of this project, develop a water pH monitoring application for Pagoh EduHub Aquatic Centre, and evaluate the application’s effectiveness with the pool staff. The methodology used for this project is Waterfall, which includes the phases of requirements gathering, system design, implementation, validation, and maintenance. If the pH levels go outside of the acceptable range, staff members can get warnings on their mobile devices using Blynk. The application helps staff monitor the pH of water effectively, minimizes the need for manual checks, and guarantees a fun and safe swimming experience for all users.